A Q Method Approach to Evaluating Farmers’ Perceptions of Foot-and-Mouth Disease Vaccination in Vietnam - Truong, Dinh Bao; Binot, Aurélie; Peyre, Marisa; Nguyen, Ngoc Hai; Bertagnoli, Stéphane; Goutard, Flavie Luce (Frontiers in Veterinary Science, 2017)
This study aims to explore the farmers’ perceptions of foot-and-mouth disease (FMD) vaccination using a reflexive research method called Q methodology. A structured sample was composed of 46 farmers selected according to gender, farming experience, level of education, and production type. Statements relevant to the farmers’ perceptions of and attitudes toward FMD vaccination, related to confidence, logistics, costs, and impacts of vaccination were developed. Results were analyzed by principal component analysis and factor analysis. The influence of demographics and characterized variables on the respondent’s contribution to each factor was also tested. Regarding the different beliefs and behavior toward FMD vaccination, the common perceptions held by Vietnamese cattle and pig farmers were divided into three discourses named Confidence (24 subjects), Belief (12 subjects), and Challenge (6 subjects). The identified discourses represented 57.3% of the variances. Consensus points were found, such as the feeling of being more secure after FMD vaccination campaigns; the fact that farmers take vaccination decisions themselves without being influenced by other stakeholders; the opinion that FMD vaccination is cheaper than the costs of treating a sick animal; and that vaccines provided by governmental authorities are of high quality. Part of the studied population did not consider vaccination to be the first choice strategy in prevention. This raises the question of how to improve the active participation of farmers in the FMD vaccine strategy. Taking into consideration farmers’ perceptions can help to implement feasible vaccination strategies at the local level.